Hip and Pelvic Floor Muscle Strength in Women With and Without Urgency and Frequency-Predominant Lower Urinary Tract Symptoms. Issue 3 (July 2021) - Foster, Stefanie N.; Spitznagle, Theresa M.; Tuttle, Lori J.; Sutcliffe, Siobhan; Steger-May, Karen; Lowder, Jerry L.; Meister, Melanie R.; Ghetti, Chiara; Wang, Jinli; Mueller, Michael J.; Harris-Hayes, Marcie
Abstract : Background: Urgency and frequency are common lower urinary tract symptoms (UF-LUTS) in women. There is limited evidence to guide physical therapist-led treatment. Objectives: To compare hip and pelvic floor muscle strength between women with and without UF-LUTS. We hypothesized women with UF-LUTS would demonstrate (1) diminished hip external rotator and abductor strength and (2) equivalent pelvic floor strength and diminished endurance compared with controls. Study Design: A matched case-control study. Methods: Women with UF-LUTS (cases) and controls were matched on age, body mass index, and vaginal parity. An examiner measured participants' (1) hip external rotator and abductor strength via dynamometry (maximum voluntary effort against fixed resistance) and (2) pelvic floor muscle strength (peak squeeze pressure) and endurance (squeeze pressure over a 10-second hold) via vaginal manometry. Values were compared between cases and controls with paired-sample t tests (hip) or Wilcoxon signed rank tests (pelvic floor). Results: In 21 pairs (42 women), hip external rotation (67.0 ± 19.0 N vs 83.6 ± 21.5 N; P = .005) and hip abduction strength (163.1 ± 48.1 N vs 190.1 ± 53.1 N; P = .04) were significantly lower in cases than in controls. There was no significant difference in pelvic floor strength (36.8 ± 19.9 cmH2 O vs 41.8 ± 21.0 cmH2 O; P = .40) or endurance (234.0 ± 149.6 cmH2 O × seconds vs 273.4 ± 149.1 cmH2 O × seconds; P = .24). Conclusion: Women with UF-LUTS had weaker hip external rotator and abductor muscles, but similar pelvic floor strength and endurance compared with controls. Hip strength may be important to assess in patients with UF-LUTS; further research is needed.